Scattering by cracks in a conducting surface. Issue 3 (2nd April 2020) - Jacobs, Ralf T.; Kost, Arnulf
Abstract : Purpose: The purpose of this study is the formulation of an efficient method to compute and analyse the scattering characteristics of cracks or grooves in a conducting object, where the size of the crack is significantly larger than the wavelength of an incident plane wave. Design/methodology/approach: A hybrid finite element-boundary element procedure is formulated for the computation of the scattering properties of the object, where the fast multipole method is used in the boundary integral formulation. The basic fast multipole procedure is enhanced by utilising a fast Fourier transform-based convolution algorithm for the computation of the interactions between groups of source and field elements. Findings: The algorithm accelerates the evaluation of the group interactions and enables the reduction of the memory requirements without introducing an additional approximation into the procedure. Originality/value: The fast multipole method with convolution algorithm shows to be more efficient for the computation of scattering problems with a large number of unknowns than the conventional procedure.